Multiphoton Above Threshold Effects in Strong-Field Fragmentation - Madsen, C. B.; Anis, F.; Madsen, L. B.; Esry, B. D. (My University, 2012)
We present a study of multiphoton dissociative ionization from molecules. By solving the time-dependent Schrödinger equation for H+2 and projecting the solution onto double continuum scattering states, we observe the correlated electron-nuclear ionization dynamics in detail. We show—for the first time—how multiphoton structure prevails as long as one accounts for the energies of all the fragments. Our current work provides a new avenue to analyze strong-field fragmentation that leads to a deeper understanding of the correlated molecular dynamics.